Uji Potensi Fungi Endofit dalam Pengendalian Penyakit Busuk Pucuk Pada Anggrek Phalaenopsis amabilis (L.) Blume - , KHATERINE, Dr. Rina Sri Kasiamdari ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Phalaenopsis amabilis (L.) Blume or moth orchid is Indonesia native orchid. In its cultivation, crown rot which caused by F.oxysporum is one of diseases that usually attack P. amabilis. This research aimed to isolate endophytic fungi from P. amabilis roots, to asses their potency in inhibiting F.oxysporum growth in vitro and to asses the effect of endophytic fungi in increasing P. amabilis seedlings resistance against crown rot disease in vivo. The experiment of antagonist test was arranged in complete randomized design by three replications. The in vitro antagonist test was done on PDA and the parameter was percentage inhibitation of F.oxysporum growth by endophytic fungi. Antagonism in vivo test was done on P. amabilis seedlings of six months old, in 8 weeks incubation with parameters were disease intensity, and length and width of P. amabilis seedlings leaves. Collected data were analyzed by one way anova and DMRT. Result showed that three endophytic fungi were isolated, which were Sistotrema sp. Ceratorhiza sp. and Moniliopsis sp., in vitro antagonism test result showed that Moniliopsis sp. had the highest inhibition percentage (71,80%) among Ceratorhiza sp. (67,70%) and Sistotrema sp. (54,87%), whereas in antagonism in vivo test, all endophytic fungi did not show reduction of F.oxysporum infection intensity, but it was significantly reduce percentage colonisation of F.oxysporum hyphae in P. amabilis roots from 75,7% with inoculation F. oxysporum only became 54,3%, 53%, 45,33% with inoculation of Sistotrema sp., Moniliopsis sp. and Ceratorhiza sp. respectively. The used of endophytic fungi did not show significant effect on the length and width of P. amabilis leaves.